Análise dos aspectos legais e normativos do uso de fotografias contidas em teses e dissertações disponíveis na BDTD/IBICT - Silva, Priscila da (Universidade Federal de São Carlos, 2016)
This study investigated the ownership of photographs contained in theses and dissertations collected in BDTD / IBICT, with the beginning of his reflections the current scenario, known as the information society, characterized by intense information exchange. In this scenario, the user information need to be increasingly aware of how appropriates the information, seeking to be based on ethical behavior. Such behavior involves knowledge of how various content available on the Internet, knowledge of the law governing copyright and uses of intellectual works in Brazil and the knowledge of the citation and reference standards. The methods used for development work were the bibliographic and documentary research. It was found that there is a low use of photographs in the public domain and, in some cases, the guidelines of the rules were not followed.
Analysis of legal and regulatory aspects of the use of photographs contained in theses and dissertations available in the BDTD/IBICT
Keywords: Apropriação da informação; Direitos autorais; Citação de ilustração; Referência de ilustração; Licenças de uso; Appropriation of information; Copyright; Illustration quote; Illustration reference; License usage; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO